Stone tools of prehistoric Arabia (Oxford)
viii, 191 sayfa
Keywords: “This volume presents the proceedings from the special one-day session on the stone tools of prehistoric Arabia, held during the Seminar for Arabian Studies (Leiden 2019)“ --